ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP PENGARUH HARGA PADA USAHA TANAMAN HIAS BUNGA SUBUR - Veren Putri Shamaya (Trending: Jurnal Manajemen dan Ekonomi, 2023)
The use of houseplants is growing day by day. This happens because during the pandemic, many residents are required to work and carry out their activities at home or at home. As a result of this the people began to grow houseplants. There are several things that result in an increase in demand for ornamental plants, namely from trends to business opportunities. The more enthusiasts, the need for houseplants is higher. According to the existing problems, research was carried out on the information system for selling ornamental plants using the website. Thus the sellers and buyers have a container to buy and sell plants. The purpose of this study is to find out a good accounting information system in the Fertile Flower Ornamental Plant Business. The form of research carried out in this mini-research is in the form of documentation and obeservation on the Fertile Flower Ornamental Plant business.